First-generation predictors of biological protein phase separation. (October 2019) - Vernon, Robert M; Forman-Kay, Julie D
Highlights: Phase separation can be predicted by multiple methods based on diverse approaches and underlying mechanistic assumptions. These methods generally overlap in predicting a small set of proteins, including a subset of RNA-binding proteins. No individual predictor captures the full range of known phase-separating proteins. Functional associations of predicted proteins differ according to predictor basis. These observations support the multiplicity of physical mechanisms used in biology to drive phase separation. Abstract : Biological condensates, including membraneless organelles, can consist of hundreds of proteins, and it is important to identify which proteins are driving condensation and which proteins have evolved to regulate protein compartmentalization by liquid–liquid phase separation. Predictors that have been used for this purpose have emerged from a variety of perspectives and have diverse designs, sequence dependencies, and physical bases. Here, we describe, compare, and contrast a range of first-generation phase-separation predictors currently available to demonstrate their overlapping and unique predictions and to highlight the need for second-generation predictors that would more comprehensively incorporate the multiple features associated with phase separation.